The Role of SIRT1 in Diabetic Kidney Disease - Yacoub, Rabi; Lee, Kyung; He, John Cijiang (Frontiers in Endocrinology, 2014)
Sirtuins (SIRTs) are members of the silent information regulator 2 (Sir2) family. In mammals, of the seven known SIRTs, SIRT1 function is most studied and has been shown to regulate wide range of cellular functions that affect metabolic homeostasis and aging. SIRT1 exerts anti-apoptotic, anti-oxidative, and anti-inflammatory effects against cellular injury, and protects the cells through the regulation of mitochondrial biogenesis, autophagy, and metabolism in response to the cellular energy and redox status. SIRT1 also promotes vasodilation and protects vascular tissues. In humans and animal models with diabetic kidney disease, its expression tends to be decreased in renal cells, and increased expression of SIRT1 was found to play a renal protective role in animal models with diabetic kidney disease. In this review we discuss the role and potential mechanisms by which SIRT1 protects against DKD.